The Influence of Economic Status and Resilience on Family Caregiver’s Anxiety of Schizophrenia Patients During Covid 19 Pandemic at Plosoklaten Community Health Center Kediri - Dhenok Sekarningrum; Tatik Imadatus Sa’adati; Nur Aziz Afandi (International Conference on Psychology and Education (ICPE), 2023)
Schizophrenia is a severe mental disorder characterized by strange behavior, delusions and hallucinations. To fullfill the schizophrenia needs, of course, need others helps. The other words, the patients who are caring at home, Family caregiver has important roles in caring them. The aim of this research is to know the influence of Economic status and Resilience on family caregiver anxiety of schizophrenia patients during covid 19 Pandemic at Plosoklaten Community Health Center Kediri. The subjects of the research are 50 family givers of schizophrenia patients. There are 3 variables in this research. Variable 1 is using the Economic Status Scale, Variable 2 is using a resilience scale, and Variable 3 is measuring anxiety by the DASS test. The significance value of X1 and X2 on Y is 0.001 <0.05 and the calculated F value is 8.254 > F table 3.18, which means that there is a simultaneous effect between economic status (X1) and resilience (X2) on anxiety. The value of 2 is 0.260 which is equal to 26%. So, it means that there is a simultaneous influence between economic status (X1) and resilience (X2) on anxiety (Y) by 26%. While the remaining 100% - 26% = 74% is influenced by other variables outside of this research.